PRESENTATION POTENTIAL USING IN PEDAGOGICAL INTERACTION PROCESS - Olga V. Ershova (Obrazovanie i Nauka)
The given article is aimed at considering multimedia presentation potential and its influence on strengthening classroom teacher-student interaction. In the article the importance of using this kind of activity in the study process is pointed in connection with educational state policy on the one hand. On the other hand, gained students’ skills as a final result of work with presentations met employers’ demand for both parent and world labour-markets and bring competitive benefit to the candidates. Scientific novelty and results. Multimedia presentation is considered as a specific complex of classroom activities. The students are oriented on the self analysis and presentation assessment. It is shown that well-organized process of peer students’ assessment allows to simultaneously helping in solving the didactic and methodical problems. To this purpose the system of assessment criteria should be developed. It has to be clear for students for making assessment feasible and time-saving. The example of a possible variant of criteria system is described; quality of the presentations prepared by students can be defined based on such system criteria. The author also analyzed software products of the three main platforms (Windows, Linux, MacOs) which have different tools and allow to follow users’ needs for creating presentations. In the article there is a comparative table of the two most popular software development: the program Microsoft PowerPoint and the web-service Prezi for realizing the relevance of their use in the study process. Practical significance of the present article concludes in author’s suggestions of some recommendations for presentation potential use as a tool of improving pedagogical interaction process with contemporary students.